Inhibitory Effect of Medicament Camphorated Parachlorophenol to Bacteria in Chronic Apical Abscess - Malinda, Yuti; Prisinda, Diani (Applied mechanics and materials, 2022)
Chronic apical abscesses are triggered by bacteria belonging to the Staphylococcus and Streptococcus genus. The use of adequate endodontic treatments and materials is essential for long-term performance treatment. Camphorated parachlorophenol has high antibacterial activity, evaporating continuously and diffusing throughout the root canals. This study aims to determine the inhibitory effect of camphorated parachlorophenol on Staphylococcus and Streptococcus in a chronic apical abscess. This experimental study using the well-diffusion test and the Davis and Stout inhibitory zone classification. Six Staphylococcus and one Streptococcus isolated from the apical abscess root canal are used in this study. The 50% and 75% camphorated parachlorophenol with chlorhexidine gluconate 2% as a positive control and Dimethyl sulfoxide (DMSO) as a negative control were test the sensitivity of bacteria Staphylococcus cohnii, Staphylococcus epidermidis, Staphylococcus haemolyticus, Staphylococcus hominis, Staphylococcus saprophyticus, Staphylococcus warneri and Streptococcus salivarius. The inhibitory zone diameter was calculated for each concentration and bacteria. Staphylococcus and Streptococcus genus were found to be 100 percent highly susceptible to camphorated parachlorophenol, while Staphylococcus genus were 50 percent and 75 percent extremely susceptible. The inhibitory zone of camphorated parachlorophenol 50 percent was slightly higher than the inhibitor zone of camphorated parachlorophenol 75 percent. The highest significant ratios of camphorated parachlorophenol 50 percent and 75 percent inhibitory zone were found in Staphylococcus hominis, Staphylococcus warneri, and Staphylocccus saprophyticus. Antibacterials in chemical compounds affect bacteria through three mechanisms: damaging cell membranes containing lipids, modifying proteins, or modifying DNA. In conclusion, camphorated parachlorophenol as a medicament has an inhibitory effect to Staphylococcus and Streptococcus genus. Staphylococcus epidermidis, Staphylococcus warneri, Staphlyococcus saprofiticus, Staphlococcus haemoliticus, Staphlyococcus cohnii, Staphlyococcus hominis, and Streptococcus salivarius were highly susceptible to camphorated parachlorophenol 50% and 75%.